Effects of Nutrients Concentration on Phytoplankton Abundance in The Halmahera-Molucca Sea - Meirinawati, Hanny; Fitriya, Nurul (Indonesian Institute of Sciences, 2018)
The availability of nutrients in the ocean is essential for the growth and accumulation of phytoplankton biomass. The input nutrients can then changes its ratio which may affect the species composition of phytoplankton communities and higher trophic level biotas. The effects of nutrients on phytoplankton abundance are very important to be studied due to its role as limiting factors for phytoplankton growth. Besides that, these two variables are most important factors in measuring aquatic productivity. This study aims to analyzed composition and abundance of phytoplankton and its relationship with dissolved inorganic nutrients in the Halmahera-Molucca Sea. This research was conducted in November 2015 covering 8 sampling station within the Halmahera-Molucca Sea. Water quality parameters, such as pH was measured using potentiometic method, dissolved oxygen (DO was measured using titrimetric method), and nitrate, nitrite, ammonium, phosphate and silicate, were measured using the colorimetric method. The water samples were taken using Rosette sampler and then filtered using hand net plankton with size 20 ÃŽÂ¼m to obtain the phytoplankton. Plankton composition and abundance were then determined by microscopic analysis. The result showed that ammonium positively correlated with phytoplankton abundance (r=0.9133 at p<0.01). The correlation between nutrients and phytoplankton show that each genus has a preference for different nutrients. The presence of ammonium significantly increase the phytoplankton abundance from genus Chaetoceros, Nitzchia, Climacodium, Ceratium, Eucampia, Lauderia, Protoperidinium, and Rhizosolenia. On the other hand, phosphates increase the phytoplankton abundance from genus Coscinodiscus although not significantly. Besides, silicates increase the phytoplankton abundance from genus Thalassiothrix, Bacteriastrum, Skletonema, and Hemiaulus while nitrates increase the phytoplankton abundance from genus Alexandrium